Anti-Oral Microbial Activity and Anti-Inflammatory Effects of Rosmarinic Acid in Lipopolysaccharide-Stimulated MC3T3-E1 Osteoblastic Cells on a Titanium Surface - Moon-Jin Jeong; Do-Seon Lim; Kyungwon Heo; Soon-Jeong Jeong (The Korean Society of Dental Hygiene Science, 2020)
Background: The purpose of this study was to investigate the anti-oral microbial activity and anti-inflammatory effects of rosmarinic acid (RA) in lipopolysaccharide (LPS)-stimulated MC3T3-E1 osteoblastic cells on a titanium (Ti) surface during osseointegration, and to confirm the possibility of using RA as a safe natural substance for the control of peri-implantitis (PI) in Ti-based dental implants.Methods: A disk diffusion test was conducted to confirm the antimicrobial activity of RA against oral microorganisms. In order to confirm the anti-inflammatory effects of RA, inflammatory conditions were induced with 100 ng/ml of LPS in MC3T3-E1 osteoblastic cells on the Ti surface treated with or without 14 μg/ml of RA. The production of nitric oxide (NO) and prostaglandin E2 (PGE2) in LPS-stimulated MC3T3-E1 osteoblastic cells on the Ti surface was confirmed using an NO assay kit and PGE2 enzyme-linked immunosorbent assay kit. Reverse transcription polymerase chain reaction and western blot analysis were performed to confirm the expression of interleukin (IL)-1β and tumor necrosis factor (TNF)-α in total RNA and protein. Results: RA showed weak antimicrobial effects against Streptococcus mutans and Escherichia coli, but no antimicrobial activity against the bacteria Aggregatibacter actinomycetemcomitans and the fungus Candida albicans. RA reduced the production of pro-inflammatory mediators, NO and PGE2, and proinflammatory cytokines, TNF-α and IL-1β, in LPS-stimulated MC3T3-E1 osteoblastic cells on the Ti surface at the protein and mRNA levels.Conclusion: RA not only has anti-oral microbial activity, but also anti-inflammatory effects in LPS-stimulated MC3T3-E1 osteoblasts on the Ti surface, therefore, it can be used as a safe functional substance derived from plants for the prevention and control of PI for successful Ti-based implants.